Challenges and Implications of Indonesia's Strategic Position in Maritime Security - Emil Mahyudin; Gilang Nur Alam; RMT Nurhasan Affandi; Windy Dermawan; Fuad Azmi (Universitas Sultan Ageng Tirtayasa, 2022)
The primary goal is to evaluate the regional maritime security problems that Indonesia is now confronting. As is well known, with the beginning of the twenty-first century came the introduction of a new word in regional maritime architecture. The significance of the sea in the current era of globalization has prompted all countries to manage their maritime interests and share concerns in a collaborative, cooperative, and inclusive manner, according to the United Nations. Throughout the period, Indonesia grew more connected than it had been previously. Indonesia, located in Southeast Asia, rose to prominence as a worldwide power in this century. Of course, as a result of its actions, new issues in maritime security have arisen. International relations, maritime cooperation, port and shipping sectors, as well as comparative politics and international relations, as well as Southeast Asian politics and society, will find this article of interest on the topic of maritime security.